2002
DOI: 10.2337/diabetes.51.3.813
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Microvascular Adaptation to Myocardial Metabolic Demand Can Be Restored by Inhibition of Iron-Catalyzed Formation of Oxygen Free Radicals in Type 2 Diabetic Patients

Abstract: Dilation of coronary vessels is impaired in diabetic patients when myocardial metabolic demand is increased. Deferoxamine (DFX) restores a normal dilation of epicardial coronary arteries. To assess the effects of DFX on metabolic coronary microvascular dilation in type 2 diabetic patients, coronary blood flow was measured using intracoronary Doppler and quantitative angiography in 17 type 2 diabetic patients with normal coronary arteries and without any other coronary risk factors. Measurements were made at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Thus, some animal experimental data regarding the effect of manipulating iron stores on atherosclerosis and human data showing improvement of vascular structure and function following iron depletion (16,17,72,75) are both consistent with the theory that iron contributes to the development of vascular disease. However, the current epidemiological data associating iron stores with either atherosclerosis or coronary heart disease (reviewed in 78) do not fully support this hypothesis.…”
Section: A Iron Depletion and Diabetic Metabolic Controlsupporting
confidence: 52%
See 2 more Smart Citations
“…Thus, some animal experimental data regarding the effect of manipulating iron stores on atherosclerosis and human data showing improvement of vascular structure and function following iron depletion (16,17,72,75) are both consistent with the theory that iron contributes to the development of vascular disease. However, the current epidemiological data associating iron stores with either atherosclerosis or coronary heart disease (reviewed in 78) do not fully support this hypothesis.…”
Section: A Iron Depletion and Diabetic Metabolic Controlsupporting
confidence: 52%
“…In type 2 diabetic patients, coronary artery responses to cold stress testing improved substantially after deferoxamine administration (16). Similarly, iron chelation was shown to ameliorate the endothelial dysfunction of patients with coronary heart disease (17).…”
Section: A Iron Depletion and Diabetic Metabolic Controlmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been suggested that oxidative stress, which is increased in diabetes (27), can depress endothelium-mediated dilation by inactivation of nitric oxide (28). Indeed, an antioxidant agent could restore endothelium-dependent dilation in diabetes (5,29,30). On the other hand, it has been shown that there was a failure of coronary blood flow to adequately increase in diabetic patients because of impaired metabolic microvascular dilation (26,31), which could mask the ability of epicardial arteries to dilate in the absence of flow velocity increase.…”
Section: Cpt Response As a Witness Of Coronary Endothelial Dysfunctionmentioning
confidence: 99%
“…The incidence of diabetes, postprandial serum insulin and pancreatic insulin sensitivity, i.e., beta cell function were al improved in subjects with previous phlebotomy treatment [143] . Iron removal also improved coronary vascular dysfunction in patients with T2DM [144] and endothelial function in patients with known coronary artery disease and in subjects with primary iron overload [145,146] . Blood donations were linked to insulin sensitivity even in healthy subjects [46] .…”
Section: What Is the Therapeutic Potential Of Modulating Iron Stores mentioning
confidence: 99%